Propofol Augments Paclitaxel-Induced Cervical Cancer Cell Ferroptosis In Vitro - Zhao, Meng-Yun; Liu, Pan; Sun, Chen; Pei, Li-Jian; Huang, Yu-Guang (Frontiers in Pharmacology, 2022)
Introduction: Cervical cancer is common in women. The present standardized therapies including surgery, chemotherapy and radiotherapy are still not enough for treatment. Propofol is the most commonly used intravenous anesthetic agent for induction and maintenance of anesthesia and has been shown to exert anti-malignancy effects on cancer cells, inducing oxidative stress and apoptosis. However, the biological effects of propofol have not yet been systematically assessed. In this study, we examined the ferroptosis-related changes caused by propofol and the chemotherapeutic agent paclitaxel besides apoptosis in vitro. Methods: Cervical cancer cell lines (C-33A and HeLa) were treated with propofol alone (1, 2, 5, 10, and 20 µg/ml) or in combination with paclitaxel (0.5, 1, and 5 µg/ml). The viability was assessed using cell counting kit-8 (CCK8), apoptosis was detected by flow cytometry, morphological changes of mitochondria were examined using transmission electron microscope (TEM), cellular reactive oxygen species (ROS) and intracellular ferrous ions were determined by fluorescence microscope or confocal microscopy. The expression and cellular localization of apoptosis and ferroptosis-related molecules were detected by Western blot and multiplex immunohistochemistry (mIHC), respectively. Calcusyn software was used to determine whether propofol has synergistic effect with paclitaxel. Results: Propofol and paclitaxel inhibited C-33A and HeLa cell viability. There were also synergistic effects when propofol and paclitaxel were used in combination at certain concentrations. In addition, propofol promoted paclitaxel induced cervical cancer cell death via apoptosis. ROS level and Fe2+ concentrations were also influenced by different drug treatments. Furthermore, propofol, PIE, and paclitaxel induced ferroptosis-related morphological changes of mitochondria in C-33A and HeLa cells. Ferroptosis-related signaling pathways including SLC7A11/GPX4, ubiquinol/CoQ10/FSP1, and YAP/ACSL4/TFRC were found changed under drug treatments. Conclusion: Propofol showed synergistic anti-cancer effects with paclitaxel in cervical cancer cells. Propofol and paclitaxel may induce ferroptosis of cervical cancer cells besides apoptosis.